PERAN PEMAHAMAN MAHARAH KALAM PADA PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH KEAGAMAAN (MAK) - Mufidah, Nuril; Attaqi, Khonsa Fillah; Amrullah, Hasyim (Proceeding of International Conference on Islamic Education (ICIED), 2022)
This article was written to know the concept of kalam's comprehension in MAK and the kalam's role in the MAK's Arabian-language learning system to give its students an excellent Arabic potential. The article was written using qualitative research methods by observing and analyzing the activity in MAK along with data reports and effective kalam methods. These observations and analyses come from an interview with one of the teachers in MAK and the writer's personal experience as an alumnus of the school. From comments and critiques done, MAK has a system of modern salaf learning by confusing a system of salaf learning, by examining ancient books such as fiqh, ushul fiqh, tafsir, hadith, and other modern studies by reading contemporary books such as hadith, interpretation, Tarikh (history) and apply learning methods according to the current education curriculum. Students are required to be well-versed in Arabic to understand the material of the books. In addition, MAK had a vision of making learners academicians and non-academicians. This is to ensure high confidence in learners who are competent and can accomplish much. One Arabic skill that needs to be mastered in the students' self-confidence is maharah kalam. Maharah kalam has an essential role in the Arabic mastery of students in mak both in terms of understanding materials in the teaching-learning activities (KBM) and in terms of practice in speaking to boost their confidence. Therefore, many of the methods applied to support their understanding of their social work are the muhadatsah, the reading of the book in front of the class, listening to the audiolingual and watching the Arabic videos, Tuesday morning, following talent and interest, and actively participating in the competition. The methods used are expected to be effective in developing the student council to achieve the MAK's vision and mission.